1994
DOI: 10.1161/01.str.25.6.1122
|View full text |Cite
|
Sign up to set email alerts
|

Baseline silent cerebral infarction in the Asymptomatic Carotid Atherosclerosis Study.

Abstract: Background and Purpose In a group of patients with highgrade asymptomatic carotid artery stenosis, we prospectively determined the prevalence and radiological characteristics of clinically asymptomatic brain infarction evident on computed tomography. Risk factors and extent of carotid disease were also determined.Methods Patients randomized into the Asymptomatic Carotid Atherosclerosis Study (ACAS) underwent a neurological history, a detailed stroke/transient ischemic attack questionnaire, and a detailed neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
65
2
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 46 publications
6
65
2
2
Order By: Relevance
“…this suggests that the progression of arteriosclerotic change in the brain was paralleled by systemic atherosclerosis and conversely that assessment of systemic atherosclerosis could predict latent damage to the brain, almost similar findings reported by various investigators from different countries. 3,4,5,11,12,13,14 The characteristics of SCI lesions were similar to the results of other studies. 13,15,16,17 that is, they were usually smaller than 1cm,were mostly in the basal ganglia (P<0.01) and had a higher incidence in right cerebral hemisphere (P<0.05) signified non-dominant hemisphere predominance for SCI.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…this suggests that the progression of arteriosclerotic change in the brain was paralleled by systemic atherosclerosis and conversely that assessment of systemic atherosclerosis could predict latent damage to the brain, almost similar findings reported by various investigators from different countries. 3,4,5,11,12,13,14 The characteristics of SCI lesions were similar to the results of other studies. 13,15,16,17 that is, they were usually smaller than 1cm,were mostly in the basal ganglia (P<0.01) and had a higher incidence in right cerebral hemisphere (P<0.05) signified non-dominant hemisphere predominance for SCI.…”
Section: Discussionsupporting
confidence: 87%
“…Similar type of findings were also observed by other investigators. [3][4][5][12][13][14][15]21 age, hypertension and plaque score strongly and independently correlated with the occurrence of SCI of brain, compatible with results of other studies. 22,23,24 Conclusion Silent cerebral infarction (SCI) detected incidentally by MRI is considered the preliminary stage of accidental stroke and assumed to be secondary to atherosclerotic vascular disease (ASVD).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…1,5 Previous MRI studies also suggested that right-sided strokes are more often unnoticed because they found more right-sided silent infarcts in patients with carotid stenosis and atrial fibrillation. 6,7 An important advantage of MRI studies is that these not only detect clinical strokes but also clinically silent infarcts, thereby providing a better estimate of the true distribution of left-and right-sided infarcts. To our knowledge, no study has compared the distribution of clinical strokes with that of MRI-defined cerebral infarcts within an unselected community-dwelling population.…”
mentioning
confidence: 99%
“…Die [14]. Auf der anderen Seite besteht beim Nachweis solcher stummer Ischämien häufig die Schwierigkeit, dass das Infarktalter nicht genauer angegeben werden kann.…”
Section: Bewertung Der Evidenzunclassified